Synergistic inhibitory activity of Glycyrrhizae Radix and Rubi Fructus extracts on biofilm formation of Streptococcus mutans - Youngseok Ham; Tae-Jong Kim (BMC, 2023)
Abstract Background Streptococcus mutans is a bacterium that causes oral diseases. Plaque, a biofilm produced by S. mutans and other bacteria, makes it difficult to remove cariogenic oral microorganisms, including biofilm producers. Glucan synthesis by glucosyltransferase is one of the mechanisms underlying plaque formation. This study demonstrates the effectiveness of inhibiting biofilm formation by interfering with the glucosyltransferase activity of S. mutans using edible herbal medicines. Methods This study investigated the inhibitory activity of Glycyrrhizae Radix extract, Rubi Fructus extract, glycyrrhizin from Glycyrrhizae Radix, and ellagic acid from Rubi Fructus against glucosyltransferase activity of S. mutans. Enzyme kinetic analysis identified the mechanism by which glycyrrhizin and ellagic acid inhibit enzyme activity. Results The conditions for synergistically inhibiting biofilm formation by combining Glycyrrhizae Radix and Rubi Fructus extracts were identified. Biofilm formation was also synergistically inhibited by mixing their respective active constituents, glycyrrhizin and ellagic acid. Glycyrrhizin and ellagic acid inhibited glucosyltransferase via noncompetitive and uncompetitive mechanisms, respectively, indicating that they inhibit it via distinct mechanisms. Conclusions This study presents an effective oral hygiene method using the synergistic activity of two natural plant extracts to inhibit biofilm formation through different inhibitory mechanisms against glucosyltransferase of S. mutans.